Implementación de la auditoría interna y su relación en la gestión institucional de la Municipalidad Distrital de Punchana año 2024 - Correa Ayambo, Angela Milagros (2025)
Internal audits are strategic, dynamic and eloquent evaluations, so that there is a rational relationship between institutional management. The current thesis, carries out an investigation to determine how it relates the implementation of internal audit and institutional management in the District Municipality of Punchana Year 2024. With this purpose, the present investigation was carried out by its nature: Quantitative, by its level: Explanatory-Causal. Likewise, it is at the following level: correlational and design: non-experimental. The research ends with the implementation of the internal audit is related to the management institutional in the District Municipality of Punchana Year 2024, demonstrated with the Correlation Coefficient r = 0.769; and the Bilateral Significance = 0.003 obtained in Table18. Likewise, it has been verified that the specific hypothesis 1. Internal audit planning is related to the achievement of institutional management objectives in the District Municipality of Punchana year 2024, having obtained a Correlation Coefficient r = 0.604 and the Significance Bilateral = 0.001 obtained in Table 19. On the other hand, in the specific hypothesis 2. The application of internal audit techniques is related to the development of institutional management policies in the District Municipality of Punchana Year 2024, having obtained a Correlation Coefficient r = 0.711; and the Bilateral Significance = 0.031 obtained in Table 19. On the other hand, in the specific hypothesis 2. The application of internal audit techniques is related to the development of institutional management policies in the District Municipality of Punchana Year 2024, having obtained a Correlation Coefficient r = 0.711; and Bilateral Significance = 0.031 obtained in Table 20. Finally, in the specific hypothesis 3. The evaluation of the internal audit is related to the factual analysis of the institutional management in the District Municipality of Punchana Year 2024, having obtained a Correlation Coefficient r = 0.667; and the Bilateral Significance = 0.002 obtained in Table 21.